Research progress in the treatment and nursing of ulcerative colitis with Traditional Chinese Medicine and western medicine (溃疡性结肠炎中西医治疗及护理研究进展) - Li Dongqing (李东青); FAN Dongying (范东英); JIANG Xiaofang (蒋小芳) (中西医结合护理)
Ulcerative colitis is an immune-mediated inflammatory bowel disease characterized by recurrent diarrhea, abdominal pain, and mucous, pus, and bloody stools. Both Traditional Chinese Medicine and western medicine have their own strengths in the prevention and control of ulcerative colitis. There is an urgent need of developing effective combination of Traditional Chinese Medicine and western medicine therapy, as well as integrative nursing interventions, for the treatment of ulcerative colitis. By searching the literature at home and abroad, this paper summarized the current research status of Traditional Chinese Medicine and western medicine treatment in the diagnosis and treatment of UC and related clinical nursing practice, in order to provide a certain theoretical basis for clinical treatment and nursing of ulcerative colitis. (溃疡性结肠炎是由免疫介导的炎症性肠病, 临床症状为反复发作的腹泻、腹痛及黏液脓血便。中西医诊疗各有所长, 探索行之有效的中西医结合治疗和护理方法对提高溃疡性结肠炎疗效有着积极意义。本研究总结中西医诊疗溃疡性结肠炎的研究现况及临床护理进展, 以期为临床进一步提升溃疡性结肠炎的诊疗质量提供一定的理论依据。)